Effect of Dietary Oils with Different Fatty Acid Compositions on Serum Lipid and Gut Microbiota of Rats - Tingwei Zhu; Yiming Kuai; Xingfeng Guo; Guanhao Bu; Chenxian Yang; Fusheng Chen (Foods)
The effects of three dietary oils (rapeseed oil, camellia oil, linseed oil) with different fatty acid compositions on the growth performance, digestion and gut microbiota of SD rats after 8 weeks of feeding were studied. The serum metabolic index and liver histomorphology of rats were measured using an automatic biochemical analyzer and light microscope. Furthermore, 16S rDNA amplicon sequencing technology was used to analyze the gut microbiota. It was found that these differences in fatty acid composition had no significant effect on body fat and liver tissue. However, after digestion, the rapeseed oil group showed lowest triglyceride content (1.22 ± 0.15) and a lower LDL/HDL ratio (0.41 ± 0.02). For gut microbiota distribution, the linseed oil group showed a higher Firmicutes/Bacteroides ratio (6.11 ± 0.54) and a high proportion of Lactobacillus. These data indicate that both the unsaturated fatty acid content and n-3 unsaturated fatty acids collectively had an effect on digestion metabolism, and the influence order may be n-3 unsaturated fatty acids > unsaturated fatty acid content.